2016
DOI: 10.1016/j.chroma.2016.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Conformational plasticity of IgG during protein A affinity chromatography

Abstract: Single step elution of a protein A column with 100mM acetate pH 3.5 produced a curvilinear gradient with pH dropping steeply at first then more gradually as it approached endpoint. IgG with a native hydrodynamic diameter of 11.5 nm began to elute at pH 6.0 with a size of 9.4 nm. IgG size continued to decrease across the peak, reaching a minimum of 2.2 nm at pH 3.9. Secondary structure of early eluting IgG was only mildly affected but later eluting fractions became increasingly non-native with the 2.2 nm popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
32
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 21 publications
4
32
1
Order By: Relevance
“…Estimates of rSPA surface coverage were compared to approximations of protein A coverage on the porous glass resin Prosep (Millipore); it was inferred that surface coverage estimates for rSPA were within the expected range, and towards the low end. Apparently low protein A surface coverage coupled with IgG elution at pH 4.1 suggested that each IgG was bound to only one protein A, supporting a “single/dual site binding” theory described by Gagnon and Nian [3]. Analysis of the reflectivity data revealed layer-based model structures in which it was possible to identify distinct contributions from protein A and from IgG4.…”
Section: Discussionsupporting
confidence: 63%
See 4 more Smart Citations
“…Estimates of rSPA surface coverage were compared to approximations of protein A coverage on the porous glass resin Prosep (Millipore); it was inferred that surface coverage estimates for rSPA were within the expected range, and towards the low end. Apparently low protein A surface coverage coupled with IgG elution at pH 4.1 suggested that each IgG was bound to only one protein A, supporting a “single/dual site binding” theory described by Gagnon and Nian [3]. Analysis of the reflectivity data revealed layer-based model structures in which it was possible to identify distinct contributions from protein A and from IgG4.…”
Section: Discussionsupporting
confidence: 63%
“…This elution pH is slightly higher than would typically be expected for elution of IgG from protein A [39], [40], [41], [42]. However, recent work by Gagnon and Nian has shown that IgG may interact with protein A by a dual-site binding mechanism in typical chromatography column environments [3], with “single site bound” IgG populations eluting at a higher pH. Thus, it is possible that the packing density of rSPA crosslinked to the surface was such that each IgG4 molecule bound a single protein A ligand, resulting in near-total elution at pH 4.1.…”
Section: Resultsmentioning
confidence: 83%
See 3 more Smart Citations